2020
DOI: 10.3390/catal10080940
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Surficial Biochar Treatment on Acute H2S Emissions during Swine Manure Agitation before Pump-Out: Proof-of-the-Concept

Abstract: Acute releases of hydrogen sulfide (H2S) are of serious concern in agriculture, especially when farmers agitate manure to empty storage pits before land application. Agitation can cause the release of dangerously high H2S concentrations, resulting in human and animal fatalities. To date, there is no proven technology to mitigate these short-term releases of toxic gas from manure. In our previous research, we have shown that biochar, a highly porous carbonaceous material, can float on manure and mitigate gaseou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
0
36
0
Order By: Relevance
“…In addition to biochar being proposed as a soil amendment, recent studies have shown that surficial application of biochar onto the swine manure can reduce emissions of odorous gases (Meirkhanuly, 2019), acute releases of H2S from agitated manure (Chen et al, 2020), and reduce volatilization loss of ammonia (Maurer et al, 2017b). Biochar pH is important in this regard, and surficial treatment of an alkaline/neutral pH biochar to manure storage can change the manure pH near the manure-air interface within few days of application (Meiirkhanuly et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to biochar being proposed as a soil amendment, recent studies have shown that surficial application of biochar onto the swine manure can reduce emissions of odorous gases (Meirkhanuly, 2019), acute releases of H2S from agitated manure (Chen et al, 2020), and reduce volatilization loss of ammonia (Maurer et al, 2017b). Biochar pH is important in this regard, and surficial treatment of an alkaline/neutral pH biochar to manure storage can change the manure pH near the manure-air interface within few days of application (Meiirkhanuly et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Chen et al (2020b) reported on the use of HAP and RO biochar as being very effective in mitigating acute releases of H2S from agitated manure on a pilot-scale [59]. Up to ~80% reduction of short-term H2S emissions were reported, showing a novel biochar application pathway for potential practical application immediately prior to manure pump-out and seasonal application to the land.…”
Section: Effect On Volatile Organic Compoundsmentioning
confidence: 99%
“…The positive role of biochar in a more sustainable animal-crop production system is provided in Figure 1. Stage 1 -biochar is surficially applied to stored manure, where it mitigates the perennial environmental problem, i.e., gaseous emissions of odor and air pollutants [21][22][23][24][25][26][27]. Biochar fits a need since many marketed manure additives have not been proven effective [28].…”
Section: Introductionmentioning
confidence: 99%